Reconstructing Curriculum System for Talent Development in Electromechanical Major: A Cross-disciplinary Integration Perspective - Li, Li; Lv, Qian; Cao, Yanyan (Transactions on Economics, Business and Management Research, 2023)
In the context of technological advancements, the close integration of the electromechanical industry with fields such as the internet, IoT technology, life sciences, gene technology, and high-end aluminum manufacturing is becoming increasingly prominent. This industrial integration brings a significant contradiction between traditional talent development and the diverse talent demands. To address this challenge, reconstructing the curriculum through a cross-disciplinary integration emerges as an effective approach for talent development in higher vocational education within the electromechanical professional group.